Perlindungan Hukum Terhadap Konsumen Mengenai Peredaran Makanan Kadaluarsa Ditinjau Dari UU No. 8 Tahun 1999 Tentang Perlindungan Konsumen - Putri Wandira; Herni Widanarti; Muhyidin Muhyidin (Law, Development and Justice Review, 2023)
Food or food products, which are daily human needs, can actually plunge consumers into losses. Not a few irresponsible and negligent business actors sell and distribute expired food products. The circulation of dangerous expired food raises questions about how legal protection is for consumers and what is the responsibility of business actors for losses received. The government as a supervisory body also underlies this question with Law Number 8 of 1999 concerning Consumer Protection. The purpose of this study is to determine legal protection for consumers regarding the distribution of expired food in terms of Law Number 8 of 1999 concerning Consumer Protection and to determine the responsibility of business actors for losses suffered by consumers. This study uses an empirical juridical approach. In this study, the respondents who were used as research data sources were the Palembang Food and Drug Administration (BPOM). The data collected is through primary data in the form of interviews and secondary data through writing, books, internet and laws. The analytical method used in this study was analyzed using qualitative methods, namely data consisting of a series of words. The results of the study show that the form of legal protection for consumers and the responsibility of business actors who harm consumers have been realized with the existence of Law Number 8 of 1999 concerning Consumer Protection and other related laws and with the assistance of the Center for Drug and Food Control (BPOM). as an institution that oversees the circulation of expired food.